SPECT with [99mTc]-d,l-Hexamethyl-Propylene Amine Oxime (HM-PAO) Compared with Regional Cerebral Blood Flow Measured by PET: Effects of Linearization - Yoshiharu Yonekura; Sadahiko Nishizawa; Takao Mukai; Toru Fujita; Hidenao Fukuyama; Masatsune Ishikawa; Haruhiko Kikuchi; Junji Konishi; Allan R. Andersen; Niels A. Lassen (1988)
In order to validate the use of technetium-99m– d,l-hexamethylpropyleneamine oxime (HM-PAO) as a flow tracer, a total of 21 cases were studied with single photon emission computerized tomography (SPECT), and compared to regional cerebral blood flow (rCBF) measured by position emission tomography (PET) using the oxygen-15 CO 2 inhalation technique. Although HM-PAO SPECT and rCBF PET images showed a similar distribution pattern the HM-PAO SPECT image showed less contrast between high and low activity flow regions than the rCBF image and a nonlinear relationship between HM-PAO activity and rCBF was shown. Based on the assumption of flow-dependent backdiffusion of HM-PAO from the brain, we applied a “linearization algorithm” to correct the HM-PAO SPECT images. The corrected HM-PAO SPECT images revealed a good linear correlation with rCBF ( r = 0.901, p < 0.001). The results indicated HM-PAO can be used as a flow tracer with SPECT after proper correction.